EDUKASI DINI BAHAYA HIV/AIDS SEBAGAI UPAYA MEMBANGUN GENERASI SEHAT DI LINGKUNGAN SMPN 10 KENDARI - Rahmat Mulyadi; Suryani; Asrah Illian; Gina Sonya; Nur Aswanti Bainto; Sri Fatmawati; Yayu Wulandari Ramadan (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Kendari City faces a concerning upward trend in HIV/AIDS cases, with the youngest case detected at age 16 and a total of 283 cases in 2024. Adolescents aged 12-17 years are particularly vulnerable due to the identity-seeking phase accompanied by poor health literacy. This community service activity was conducted at SMPN 10 Kendari on June 9, 2026, aiming to improve students' knowledge about HIV/AIDS transmission, symptoms, and prevention. The method employed was counseling through lectures, Q&A, PowerPoint media, and brochures, accompanied by pre-test and post-test instruments. A total of 35 students from grades VII, VIII, and IX participated. Results showed that all participants (100%) experienced score improvement. After counseling, all students reached the 'good' category. This activity demonstrates that lecture-based education with brochure media is effective in enhancing adolescents' knowledge about the dangers and prevention of HIV/AIDS.